Analisis Perilaku Self-Harm pada Remaja: Studi Kasus pada Siswa dan Implikasinya dalam Bimbingan dan Konseling - Yasdani, Clarita Mazely; Netrawati, Netrawati (Lembaga Yasin AlSys, 2025)
This study employed a qualitative method with a case study approach to explore self-harm behavior among students at SMA Negeri 1 Kubung, Solok Regency. The research focused on three students who engaged in self-harm, with data collected through semi-structured interviews, direct observation, and supporting documentation. Interviews were conducted with attention to the subjects’ conditions and schedules to avoid disrupting their learning activities, while secondary data from books and journals were used as supplementary sources. Data analysis was carried out inductively through the stages of data reduction, narrative presentation, and conclusion drawing, with data validity ensured through source and method triangulation. The findings reveal that the primary reason students engaged in self-harm was to express emotional pain, manifested in behaviors such as hitting themselves, cutting their hands, and burning their skin. These actions provided temporary relief and a false sense of satisfaction, while the long-term negative consequences were less recognized. The study underscores the importance of guidance and counseling interventions focused on emotional support and the development of coping strategies to prevent and address self-harm behavior among adolescents in the school environment.